2008
DOI: 10.2527/jas.2007-0527
|View full text |Cite
|
Sign up to set email alerts
|

Pros and cons of automatic milking in Europe1

Abstract: During the last several decades, new milking management systems have been introduced, of which development of automatic milking (AM) systems is a significant step forward. In Europe, AM has become an established management system and has shown to be much more than milking management. Factors such as milking, milk quality, feeding, cow traffic, grazing, and animal behavior are essential elements of AM. This system offers possibilities for more frequent milking and can be adapted to lactational stage. Increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 67 publications
3
62
0
1
Order By: Relevance
“…Although not significant, lower SCC were observed in the AMS during our observation and this fact agreed with previous statements. However, increased SCC values were also reported in studies by Kruip et al (2002), Rasmussen et al (2002) and Svennersten-Sjaunja and Pettersson (2008). TGC were, however, markedly higher (P<0.05) in the AMS (51.85 x 1,000*ml), which was in agreement with the findings of Klungel et al (2000).…”
Section: Resultssupporting
confidence: 89%
“…Although not significant, lower SCC were observed in the AMS during our observation and this fact agreed with previous statements. However, increased SCC values were also reported in studies by Kruip et al (2002), Rasmussen et al (2002) and Svennersten-Sjaunja and Pettersson (2008). TGC were, however, markedly higher (P<0.05) in the AMS (51.85 x 1,000*ml), which was in agreement with the findings of Klungel et al (2000).…”
Section: Resultssupporting
confidence: 89%
“…This negative effect of an automatic milking system might be associated with the hierarchy in the herd. Optimal cow traffic is necessary if an automatic milking system is used, to obtain an optimal number of milkings (Svennersten-Sjaunja and Pettersson, 2008). When fresh-milked heifers enter the group of lactating cows, they may experience problems with reaching the automatic milking system and the automatic milking system may experience problems with adjusting to the new cow (Miller et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Wade et al (2004) found the milk yield to be 12.4% higher, but others such as Billon and Touraine (2002) have observed, in contrast, milk yield reduction. Klungel et al (2000), Rasmussen et al (2002), de Koning et al (2003, Svennersten-Sjaunja and Pettersson (2008) have reported AMS to have negative effects on milk indicators such as increase in the freezing point, in the total microbial count, in the free fatty acid content or in the somatic cell count. Klei et al (1997) have found more frequent milking in AMS (3 times a day) to result in lower milk fat and protein contents.…”
Section: Robotic Milking Somatic Cells Freezing Point Microbiologymentioning
confidence: 99%